Environmental-Based Islamic Religious Education to Shape Students' Religious Character in Elementary School. - Hasanah, Uswatun; Nasution, Srimei Nela; Nuraeni, Heni Ani (Universitas Wahid Hasyim Semarang, 2024)
AbstractEducation is not just about transmitting knowledge between teachers and students, but also forms character. The research objective focuses on the role of environmentally based Islamic Religious Education for the formation of students' religious character in elementary schools and its implications. This type of research is qualitative with a case study approach. The school's goal is to create a generation that is religious and loves the environment with a program to get used to praying Duha in congregation, reading the Koran, always implementing 5S activities (Smile, Greet, Greetings, Polite and Courteous) wherever students are, obeying the rules, aware of the importance of literacy in reading and writing, fond of exploring lots of information, orderly in disposing of rubbish in its place, and having high creativity towards students' interests, talents, environmentally based Islamic Religious Education (PAI) in forming character religious students at SDN Pekayon 16 Pagi with these things. The implication of this formation is that good ethical moral values are embedded, students can apply positive activities in everyday life. Students know how to apply positive standards and values that influence their success in education.